Continuous improvement : a leadership process for school improvement - Anderson, Erin A.; Hayes, Sonya (Leadership for school improvement (Series), 2023)
"Through this book, we seek to describe improvement science in action for educators, schools, districts, universities, and communities. This book is a venue for improvement research in education focused on the application of improvement science in educational settings. Improvement science is time-consuming and requires participants to engage in rigorous work to implement sustainable change at a systemic level. As the editors of this volume for the Leadership in School Improvement SIG book series, we hope that these chapters, written by researchers, practitioners, and leaders engaged in improvement science will help others begin their own improvement processes to achieve desired, equitable, and sustainable results for student success"--